Estrategias de afrontamiento y calidad de vida en pacientes diagnosticados con VIH en el Hospital Provincial General Docente Riobamba, período octubre 2015- marzo 2016. - Haro Gavidia, Yaijaira Nataly (2016)
Globally, 36.9 million people live with HIV, this pandemic produces a strong emotional impact in addressing physiological, socio-cultural, economic and psychological stressors that threaten their physical and mental health, so this research aims to determine the coping strategies and quality of life in patients diagnosed with HIV in Provincial Hospital of Riobamba, period October 2015 - March 2016 and to test the hypothesis: coping strategies enhance the quality of life of patients with HIV. It is a descriptive research, of non-experimental quantitative approach, type documentary and correlational – of field and cross section. The studied population consisted of 120 patients diagnosed with HIV in active state in the National Epidemiological Information System; by inclusion and exclusion criteria a sample of 39 patients was determined. Clinical observation techniques and psychological interview were applied; psychological instruments: Inventory Valuation and Coping by Cano Vindel and Tobal adapted by Nora Leibovich and Questionnaire Quality of Life WHOQOL - BREF by WHO, which allowed data collection, which were processed by Excel tables and graphs for analysis and interpretation. It was found that 73% of respondents use active coping strategies (ACS and ACME), which relates to an improved quality of life, health and sense of control, compared with 27% those who use passive coping strategies (AE) related to distress, mood disorders and impaired quality of life. 46% of patients considered their quality of life as moderately satisfactory, the alarming indicators are: low self-esteem, energy, income, social support, unsatisfactory sexual life. A psychotherapeutic plan to increase active coping strategies to improve the quality of life through cognitive behavioral techniques was developed.